The multisensory perception of flavor: Assessing the influence of color cues on flavor discrimination responses - Zampini, M; Sanabria, D; Phillips, N; Spence, C (2007)
Two experiments are reported that were designed to investigate the influence of visual color cues on people's flavor discrimination and flavor intensity ratings for a variety of fruit-flavored solutions. In Experiment 1, the participants had to associate specific flavors with solutions of various colors simply by looking at them (i.e., without tasting them). In Experiment 2, the participants tasted the solutions and had to discriminate the flavor of solutions that had been colored either 'appropriately' or 'inappropriately', or else presented as colorless solutions. The participants were explicitly informed that the colors of the solutions provided no useful information regarding the actual flavor identity of the solutions. The participants also rated the flavor intensity of the solutions. The accuracy of participants' flavor discrimination performance was significantly lower when the solutions were colored inappropriately than when they were colored appropriately (or else were presented as colorless solutions). These results show that the modulatory effect of visual cues on flavor perception can override participants' awareness that the solutions would frequently be colored inappropriately. © 2007 Elsevier Ltd. All rights reserved.